MATHEMATICAL MODEL AND CONTROL STRATEGY FOR MOOD DYNAMICS IN CHARACTERS IN THE FILM - Nurazizah Azhari, Aliza
Every person experience mood changes over hours or days, which can be self-realized or observed by others. In films, mood changes in characters can be conveyed through dialogue, narration, cinematography, and music. One of Indonesia's popular films, "Ada Apa dengan Cinta?" attracts attention with its accurate depiction of teenage life and realistic mood dynamics, prompting the author to construct a mathematical model of mood dynamics for characters in the film, analyze the characters' moods during specific scenes or events, and apply control strategies to manage their mood dynamics. The control strategies used comprise three main approaches: pole placement control, control with observer addition, and optimal control. A spring-damper model with external forces in the form of sinusoidal functions and step functions is used to model the mood dynamics of eight characters in the film. This model heavily relies on external forces representing the influence of scenes. Although the obtained RMSE values are smaller, the model is less accurate for secondary characters like Mamet but effective for the main character, Cinta. By modeling external forces as control inputs, control strategies such as pole placement control, control with observer addition, and optimal control are applied. In pole placement control and control with observer addition, choosing the real part of the pole to be twice as negative can accelerate mood stabilization without losing character responsiveness and expressiveness. The modified optimal control brings the character's mood closer to the desired value within a specified time, reduces large mood fluctuations, provides emotional stability, and lessens drastic mood declines. Each approach has its advantages and disadvantages in terms of character, mood responsiveness and stability. The study results indicate that the applied control approaches can improve the mood dynamics model of characters, especially for main characters like Cinta, and reduce the impact of scenes or events causing significant mood changes.